Taxes and bank capital structure - Schepens, Glenn (Journal of Financial Economics, 2016)
This paper shows that a reduction in tax discrimination between debt and equity funding leads to better capitalized financial institutions. The paper exploits exogenous variation in the tax treatment of debt and equity created by the introduction of a tax shield for equity. The results demonstrate that a more equal treatment of debt and equity increases bank capital ratios, driven by an increase in common equity. The change also leads to a significant reduction in risk taking for ex-ante low capitalized banks. Overall, the findings suggest that tax shields could be a valuable and innovative policy tool for bank regulators.